APPLICATION OF NEUROIMAGING TECHNOLOGY IN MILITARY - Rizki Edmi Edison (The Republic of Indonesia Defense University, 2021)
Understanding the function of the human brain at the level of cognition is a common goal of neuroscience. Neuroscience as one of the fastest-growing areas of multidiscipline that understand the biological basis for behavior through scientific research could be used in many areas, such as management, marketing, leadership, education, and military. For revealing the human mind especially soldiers as the most important part of the military, the implementation of technology to measure the brain of humans must be considered. Through this manuscript, potential uses of neuroimaging technology in the military were analyzed PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) recommendation was conducted to provide a comprehensive review of the application of neuroimaging technologies. For practical purposes, technology with advantages such as non-invasive, real-time, and mobile should be chosen. Through this study, electroencephalography (EEG), functional near-infrared spectroscopy (fNIRS), and brain ECVT (Electrical Capacitance Volume Tomography) have potential use to measure the cognitive functions of soldiers in the military. Neuroimaging technologies have potential use in the military field, especially in the level of behavioral neuroscience. By understanding how a soldier’s brain reacts to any circumstances especially those that mimic the combat situation, it has a beneficial effect on military strategy.